Cold thermal response of an amyloid oligomer differs from typical globular protein cold denaturation - Menon, Sneha; Sengupta, Neelanjana (Journal of Physical Chemistry Letters, 2019)
In contrast with the general behavior of folded proteins, the cold thermal response of amyloid assemblies is difficult to elicit with simple models. We exploit exhaustive simulations to evaluate the thermal response of a barrel-shaped model amyloid oligomer, with a distinct hydrophobic core akin to that of folded proteins. Cumulative thermal data over the range of 210-483 K indicate a sharp inflection and rise in structural stability as the temperature is decreased below the melting temperature of the water model. This is not commensurate with the equilibrium free energy profile obtained with core packing as the order parameter. However, energetic analyses and the size of their fluctuations indicate the crucial role of hydration in mediating structural transitions, beyond the expected temperature-dependent hydrophobic effect. Structural ordering of the hydration layer over bulk water is maximized at the transition and vanishes at high temperatures. This is a first direct demonstration of the microscopic influence of hydration water on the low-temperature response of an amyloid assembly close to the cryo-regime.